EDUKASI GIZI PADA IBU HAMIL SEBAGAI SALAH SATU UPAYA MENGURANGI PENINGKATAN ANGKA STUNTING - Ahmad Jupri; Asri Julianti; Eka Puspitasari; Pahmi Husain; Eka S Prasedya; Tapaul Rozi (Universitas Mataram, 2022)
The growth and development of the child is determined since the fetus is still in the womb and the amount of nutritional intake of the mother's food during pregnancy. Pregnant women who consume less food during pregnancy will have an impact on the health of the baby at birth such as stunting, growth disorders and underweight. Stunting is a condition of failure to thrive due to optimal nutritional deficiencies. The purpose of this education is to increase the knowledge of pregnant women about nutrition during pregnancy as one of the efforts for children to be born stunted. The target at the time of the visit of pregnant women was 20 pregnant women. The Educational Service method is carried out through three stages, namely planning visits, carrying out visits and delivering socialization materials. The results of the service activities show that most of the age range of pregnant women are in the 26-32 yearold range, which is 50%, then 33-39 year old group is 30%, and 19-25 year old group is 20%. Then the level of knowledge of pregnant women related to nutritional knowledge shows that the level of knowledge is sufficient by 45%, while 30% of pregnant women have good knowledge and 25% of pregnant women participants have less knowledge. During the educational activity, participants asked many questions related to efforts to maintain the health of babies and pregnant women, especially in consuming foods that contain balanced nutrition, especially for baby growth. This educational activity can increase the knowledge and understanding of pregnant women about nutrition during pregnancy as an effort to prepare before and after childbirth, especially reducing the number of stunting.